EEF2 analysis challenges the monophyly of Archaeplastida and Chromalveolata. - Eunsoo Kim (Public Library of Science (PLoS), 2008)
Background Classification of eukaryotes provides a fundamental phylogenetic framework for ecological, medical, and industrial research. In recent years eukaryotes have been classified into six major supergroups: Amoebozoa, Archaeplastida, Chromalveolata, Excavata, Opisthokonta, and Rhizaria. According to this supergroup classification, Archaeplastida and Chromalveolata each arose from a single plastid-generating endosymbiotic event involving a cyanobacterium (Archaeplastida) or red alga (Chromalveolata). Although the plastids within members of the Archaeplastida and Chromalveolata share some features, no nucleocytoplasmic synapomorphies supporting these supergroups are currently known. Methodology/principal findings This study was designed to test the validity of the Archaeplastida and Chromalveolata through the analysis of nucleus-encoded eukaryotic translation elongation factor 2 (EEF2) and cytosolic heat-shock protein of 70 kDa (HSP70) sequences generated from the glaucophyte Cyanophora paradoxa, the cryptophytes Goniomonas truncata and Guillardia theta, the katablepharid Leucocryptos marina, the rhizarian Thaumatomonas sp. and the green alga Mesostigma viride. The HSP70 phylogeny was largely unresolved except for certain well-established groups. In contrast, EEF2 phylogeny recovered many well-established eukaryotic groups and, most interestingly, revealed a well-supported clade composed of cryptophytes, katablepharids, haptophytes, rhodophytes, and Viridiplantae (green algae and land plants). This clade is further supported by the presence of a two amino acid signature within EEF2, which appears to have arisen from amino acid replacement before the common origin of these eukaryotic groups. Conclusions/significance Our EEF2 analysis strongly refutes the monophyly of the Archaeplastida and the Chromalveolata, adding to a growing body of evidence that limits the utility of these supergroups. In view of EEF2 phylogeny and other morphological evidence, we discuss the possibility of an alternative eukaryotic supergroup.